1998
DOI: 10.1093/rheumatology/37.3.300
|View full text |Cite
|
Sign up to set email alerts
|

Headache in systemic lupus erythematosus: a controlled study

Abstract: Intractable headaches, the so-called 'lupus headaches', have been long thought of as a common and characteristic manifestation of systemic lupus erythematosus (SLE). Seventy-eight patients with SLE, including 10 patients with definite central nervous system (CNS) involvement, and 89 healthy individuals matched for age, sex and socioeconomic status, were studied by a specific questionnaire addressing the characteristics and type of headache. Clinical features of SLE, neurological manifestations and treatment, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
2
9

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 0 publications
2
54
2
9
Order By: Relevance
“…Montalban et al [7] diagnosed migraine in 31% of 103 patients, tension-type headache in 20%, and cluster headache in less than 1% of the patients. A lower proportion of patients (8%) suffered from migraine in a study carried out by Sfikakis et al [8], but in this study a diagnosis of migraine required at least one episode every 2 weeks, whereas the 1988 IHS classification [9] requires five separate lifetime attacks and two lifetime attacks, respectively, for migraine without and with aura. In a more recent study carried out by Glanz et al [10], 186 SLE patients completed the San Diego Migraine Questionnaire based on IHS criteria for migraine, which has been shown to accurately distinguish between migraine and nonmigraine headache syndromes.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 73%
“…Montalban et al [7] diagnosed migraine in 31% of 103 patients, tension-type headache in 20%, and cluster headache in less than 1% of the patients. A lower proportion of patients (8%) suffered from migraine in a study carried out by Sfikakis et al [8], but in this study a diagnosis of migraine required at least one episode every 2 weeks, whereas the 1988 IHS classification [9] requires five separate lifetime attacks and two lifetime attacks, respectively, for migraine without and with aura. In a more recent study carried out by Glanz et al [10], 186 SLE patients completed the San Diego Migraine Questionnaire based on IHS criteria for migraine, which has been shown to accurately distinguish between migraine and nonmigraine headache syndromes.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 73%
“…Although its relationship with SLE is not clear, headache and migraine are reported by 32e66% of SLE patients and may have various causes, including neuropsychiatric SLE (NPSLE) [24]. A recent study of 40 SLE patients found that 70% experienced headache (tension type headache in 37.5%, migraine in 30%, cluster headaches in 2.5%, and intracranial hypertension in 5%) but there was no association with disease activity [25,26].…”
Section: Sle and Neuropathic Painmentioning
confidence: 99%
“…Эти данные противоречивы, и описано как наличие данного факта, так и его отсутствие [25][26][27]. Головная боль при СКВ развивается как в активной фазе заболевания [28], так и вне обострения [25,27].…”
unclassified
“…Вторичная головная боль у пациентов с СКВ может развиваться на фоне патологии почек [29], инфекции [30], церебрального венозного тромбоза [31,32], внутримозго-вых или субарахноидальных кровоизлияний [33,34] Возникновение головной боли при СКВ может быть связано с тревожно-депрессивными расстройствами [26,27]. У 59% пациентов она сопровождалась наличием двух и более стрессовых симптомов [26].…”
unclassified
See 1 more Smart Citation